The relationship between anxiety, shyness, ambiguity tolerance, and language learning strategies. Issue 1 (2nd January 2016) - Sadeghi, Karim; Soleimani, Maryam
Abstract: Research has indicated that there is an association between the use and choice of learning strategies and different variables like learning contexts, learner characteristics, learning experiences, language proficiency, and cultural and educational backgrounds. To add to the thriving body of knowledge in this area, the present study, therefore, was an attempt to identify the relationship between learner characteristics of shyness, anxiety, ambiguity tolerance, and language learning strategies (LLS). To this end, 132 advanced and pre-intermediate female and male students between the ages of 16 and 18 in one language institute in Iran participated in this study. All the participants were invited to fill out four questionnaires to operationalize the above constructs. The results of a one-way between-groups multivariate analysis of variance showed that the most shy, the most anxious, and the least ambiguity tolerant learners use more strategies. No significant correlation was observed between anxiety and language learning strategy use, between gender and language learning strategy use, and between proficiency and language learning strategy use. The findings of a chi-square test for independence revealed that the most ambiguity tolerant learners were the least shy and the least anxious and vice versa. In addition, advanced learners were moderately shy while pre-intermediate learners were the least shy. The findings of the study shed light on the relationship between affective factors and LLS.